Transformasi Manajemen Keuangan Dalam Menghadapi Tantangan Teknologi Di Era Digital - Mary, Hilda; Firta, Widia; Indriyenni (Riset Sinergi Indonesia (RISINDO), 2025)
The digital era has brought significant changes to various aspects of business, particularly in the field of financial management. With the development of technologies such as big data, artificial intelligence, fintech, and digital payment systems, companies are required to adjust their financial management strategies to remain competitive. This research aims to analyze how digital transformation affects financial management processes, the challenges faced, and the opportunities that can be leveraged. The research method used is a literature review from various sources including scientific journals, books, and the latest industry reports. The results show that digitalization has a positive impact on operational efficiency, financial transparency, and faster and more accurate decision-making. However, challenges such as data security, lack of competent human resources, and regulations become major obstacles. It is recommended that organizations increase investment in digital infrastructure, human resources training, and adopt appropriate technology solutions.